2017
DOI: 10.1111/gtc.12517
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cytokine and extracellular matrix mRNAs in fetal hepatic stellate cells

Abstract: In mouse fetal liver, hepatoblasts, sinusoidal endothelial cells and macrophages (or erythroblastic islands) promote differentiation and proliferation of hematopoietic cells through cell-cell interactions and secretion of cytokines and extracellular matrix factors. Until now, we have had little knowledge of the hematopoietic cytokines or extracellular matrix mRNAs expressed in hepatic stellate cells. Using p75 neurotrophin receptor (p75NTR) to mark this cell population, we sorted 12.5, 14.5 and 16.5 dpc hepati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…Other typical hepatoblast markers are listed in Table 1. Prox1,Alb,Afp,Ck8,Ck18,Ck19,Met,Hnf6,Oc2,Hnf4a,Ttr,Foxm1,Foxa2,Tbx3,Dlk1,Lgr5,Epcam,Cdh1,Trgb1,Itga6,Liv2,Prom1, Anpep Tanimizu et al, 2003;Tan et al, 2017) E-Cadherin + (Nitou et al, 2002;Nierhoff et al, 2005) EpCAM + DLK1 + (Tanaka et al, 2009) Liv2…”
Section: Hepatoblastsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other typical hepatoblast markers are listed in Table 1. Prox1,Alb,Afp,Ck8,Ck18,Ck19,Met,Hnf6,Oc2,Hnf4a,Ttr,Foxm1,Foxa2,Tbx3,Dlk1,Lgr5,Epcam,Cdh1,Trgb1,Itga6,Liv2,Prom1, Anpep Tanimizu et al, 2003;Tan et al, 2017) E-Cadherin + (Nitou et al, 2002;Nierhoff et al, 2005) EpCAM + DLK1 + (Tanaka et al, 2009) Liv2…”
Section: Hepatoblastsmentioning
confidence: 99%
“…Indeed, several cytokines/chemokines/growth factors are important for HSC proliferation, maintenance and survival, namely KITL, FLT3L, insulin growth factor (IGF), angiopoietin-3, angiopoietin-like 2, Wnt family growth factors, Ephrin2a, CSF1, EPO, CXCL12, and IL-6 -reviewed in Sauvageau et al (2004). In FL, some of these cytokines are expressed by hepatoblasts or other stromal cells, such as stellate cells or pericytes (see Table 2 and Figure 4; Charbord and Moore, 2005;Chou and Lodish, 2010;Khan et al, 2016;Tan et al, 2017).…”
Section: The Interplay Between the Developing Hepatic-hematopoietic Tmentioning
confidence: 99%
See 2 more Smart Citations
“…HSCs can fulfill some of the functions of MSCs, such as adipocytes or osteocytes differentiation. 33,34 Thus far, only Coll et al 35 reported that they could obtain HSC-like cells from newborn male fibroblastsderived human iPSC by mimicking embryonic development; those cells closely resemble primary human HSCs at the transcriptional, cellular, and functional levels and possess a gene expression profile between that of quiescent and activated HSCs.…”
Section: Hepatic Stellate Cells (Hscs)mentioning
confidence: 99%